Representação social de juventude para jovens negros em bairros populares de Vitória-ES - Tesche, Beatriz Baptista (2010)
Based on the Theory of Representations proposed by Serge Moscovici, this paper seeks to find out the social representation of the black youth on young blacks, residents in a neighborhood of mostly black people, that has a cultural production based on afro-brazilian culture. Basically, we identified the places where young people lived and how young people contribute in these places. Also, we analyzed the relationship between the black cultural production and the elements of social representation of being young, as well as, investigated the relationship between social representation of black youth and the social representation of youth in general. Our assumption, is that in neighborhoods where black culture is produced and reproduced widely, young people have black culture in the center of their youth social representation. We interviewed 12 young people between 19 and 28 years, six males and six females, residents of Fonte Grande and Piedade in Vitória / ES neighborhoods. The interviews follow a semi-structured guide in two thematic sections. First, on adolescence and youth. Secondly, about the community and youth participation. Also, it contained socioeconomic issues. The results show that social representation of participants on black youth are freedom, discipline, determination, and resistance to racism. Both men and women had the same social representation of youth but, on the other hand, the same had different results on how to articulate the social representation of youth with the social representation of gender. A second social representation was identified and it corresponds to the participants belief's on how society perceive the black community, in general, as potential dirty and dangerous criminals. Finally, in order to maintain a positive social image of black young people, participants utilized their neighborhood cultural network, where new concepts are developed to help change racism and stereotype.